Techniki rozwijające wyższe poziomy przetwarzania tekstu w kształceniu sprawności czytania wśród dorosłych - Marzec-Stawiarska, Małgorzata (Neofilolog, 2019)
The article is devoted to reading skills development among adult students of English. It presents parameters of the techniques which, according to the contemporary theories of reading processes, should teach text com-prehension efficiently. The article also shows how to incorporate these techniques into a classroom setting and presents the results of the re-search in which students, who used these techniques in practice, ex-pressed their opinions about their motivational value and efficiency.